Using WhatsApp Group & Google Meet during Online Class, Why Not? - Lina, Marisa Fran; Hidayati, Diyah Nur (Elsya : Journal of English Language Studies, 2022)
Since the Covid-19 breakout, students in all levels of education across the nation from preschool to higher education have had no choice except to learn online. The Indonesian lecturers are required to think creatively managing their class online. This qualitative study examines descriptively on the effect of the Covid-19 pandemic on the college students’ opinion in 59 students from two selected private universities in Indonesia, Salatiga and Surakarta Islamic universities. It also studies further about the merging of 2 platforms such as WhatsApp Group and Google Meet could be a solution to student boredom and misunderstanding in learning English. The data was collected using Google forms. Then, inductive analysis was used to test the data. The findings show that, despite the effects of the Covid-19 pandemic on online English classes, such as unstable signal problems and the need to be constantly in front of gadgets, the students in Salatiga and Surakarta can understand the material. They also have a good time in online English classes because the lecturers in WhatsApp Group include games, puzzles, quizzes, and other interesting activities to keep them entertained during online classes. During online learning, both lecturers and students at the University in Salatiga and Surakarta face numerous challenges, namely the need for the lecturers to be creative in class and to liven up the atmosphere, even though classes were held online due to a massive pandemic. This study recommends WhatsApp Group to be an effective platform to share information and task instructions related to the lecture and should be paired with Google Meet in scheduled online learning to obtain maximum effect for most students’ understanding toward the topic.